Proceedings of the 2015 IEEE/ACM International Symposium on Nanoscale Architectures (NANOARCH´15) 2015
DOI: 10.1109/nanoarch.2015.7180586
|View full text |Cite
|
Sign up to set email alerts
|

NEMsCAM: A novel CAM cell based on nano-electro-mechanical switch and CMOS for energy efficient TLBs

Abstract: Abstract-In this paper we propose a novel Content Addressable Memory (CAM) cell, NEMsCAM, based on both Nanoelectro-mechanical (NEM) switches and CMOS technologies. The memory component of the proposed CAM cell is designed with two complementary non-volatile NEM switches and located on top of the CMOS-based comparison component. As a use case for the NEMsCAM cell, we design first-level data and instruction Translation Lookaside Buffers (TLBs) with 16nm CMOS technology at 2GHz. The simulations show that the NEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Xue et al [53] proposed to speculatively perform address translation, based on the base-displacement address, by accessing a small L0 TLB early in the pipeline, so that the translation latency is not increased. Finally, Seyedi et al [47] proposed combining nano electro mechanical switches with CMOS technology for fully associative L1 TLBs.…”
Section: Related Workmentioning
confidence: 99%
“…Xue et al [53] proposed to speculatively perform address translation, based on the base-displacement address, by accessing a small L0 TLB early in the pipeline, so that the translation latency is not increased. Finally, Seyedi et al [47] proposed combining nano electro mechanical switches with CMOS technology for fully associative L1 TLBs.…”
Section: Related Workmentioning
confidence: 99%
“…Pai and Tabib-Azar (2014) implemented the logic gates such as all or nothing gate (AND), any or all gate (OR) and XOR gates using microplasma with operating voltage in between 5 and 40 V with foot size of 50 × 5 μ m. Sinha et al (2012) reported the inverter, NAND and NOR mechanical logic gates using body-biased Aluminum Nitride (AlN) piezoelectric MEMS switches with operating swing voltages of ±2 V. Parsa et al (2013) implemented the 2 × 1 multiplexer using laterally actuated platinum-coated polysilicon NEM relays with operating gate pulse voltage of 10.75 V and beam voltage of 1 V. Rochus et al (2013) reported the design of inverters, NAND gate and ring oscillator based on NEMS relay which works similar to CMOS-based devices. Seyedi et al (2015) proposed content addressable memory component using NEM switches and CMOS transistors to realize the translation lookaside buffers with 16 nm technology works at 2 GHz for accessing data and instructions to complete the search operation within one clock cycle. Samaali et al (2015) reported mathematical modeling and finite element method solution for electrostatic-based single pole double throw switch (SPDT) micro switch used in a wireless sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Pai and Tabib-Azar (2014) implemented the logic gates such as AND, OR and exclusive or gate (XOR) gates using microplasma with operating voltage in between 5 and 40 V with foot size of 50 m m  5 m m. Sinha et al (2012) illustrated the inverter, NAND and NOR mechanical logic gates using body-biased AlN piezoelectric MEMS switches with operating swing voltages of 62 V. Parsa et al (2013) implemented the 2x1 multiplexer using laterally actuated platinum-coated polysilicon NEM relays with operating gate pulse voltage of 10.75 V and beam voltage of 1 V. Rochus et al (2013) reported the design of inverters, NAND gate and ring oscillator based on NEMS relay, which works similar to CMOS-based devices. Seyedi et al (2015) proposed content addressable memory component using NEM switches and CMOS transistors to realize the Translation Lookaside Buffers with 16 nm technology working at 2 GHz for accessing data and instructions to complete the search operation within one clock cycle. Proie et al (2011) reported the low-power Piezo MEMS-based 3-bit analog to digital converter (ADC), which operates without any additional electronic components.…”
Section: Introductionmentioning
confidence: 99%